Design of an Extension Program for Rorak Construction as an Approach to Coffee Land Conservation in Parbuluan District, Dairi Regency - Eva Deo Vani Banjarnahor; Silvia Nora; Mawar Indah Perangin angin (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The limited adoption of rorak as a soil and water conservation technique in coffee plantations in Parbuluan District, Dairi Regency, has been associated with farmers’ limited knowledge of and attitudes toward its benefits and application. This study examined changes in farmers’ knowledge, attitudes, and implementation practices following an agricultural extension program on rorak construction for coffee-land conservation. A descriptive quantitative pretest–posttest evaluation was conducted from January to May 2026 involving 40 coffee farmers from the Immanuel and Unggul Farmer Groups. Data were collected through observations, interviews, questionnaires, and pretest and posttest assessments. Changes in knowledge were evaluated by comparing scores obtained before and after the extension activity, whereas attitudes were measured using a Likert scale. The mean knowledge score increased from 4.75 at pretest to 8.25 at posttest, representing a 3.50-point or approximately 73.7% increase. The overall attitude score reached 86%, indicating a highly positive response to rorak adoption. Furthermore, 20 farmers (50%) implemented rorak, exceeding the initial target of 30%. These post-extension improvements suggest that the program strengthened farmers’ knowledge and attitudes while encouraging the practical adoption of soil and water conservation technology. Although the design does not establish causality, the study provides context-specific evidence that locally tailored agricultural extension can support sustainable conservation practices among smallholder coffee farmers.